Profil Nutrien Nitrat dan Fosfat pada Air di Sungai Jangga, Karangasem, Bali - Syahriyani Purba; Ima Yudha Perwira; Dewa Ayu Angga Pebriani (Current Trends in Aquatic Science, 2021)
Jangga river is one of the rivers in the Bali and has important ecological function. On the other hand, the jangga also became a waste-disposal of anthropogenic activities surround the river. That could an affect to increase content of nitrate and phosphate was found in Jangga river. This study was aimed to identify the concentration of nitrate and phosphate in the water of Jangga river. This study was conducted in a descriptive method by taking samples five stations from January to February 2020. The main parameters measured are Nitrate, phosphate and other water quality parameters (turbidity, temperature, pH, TDS, TSS, DO, COD and chromium). The result of this study showed that nitrate levels were high. The value of nitrate ranged from 5.3 mg/L to 7.6 mg/L. Parameter of phosphate was found in the Jangga river is also high. The value of phosphate ranged from 0.7 mg/L to 1.3 mg/L These are affected by the sewage from anthropogenic activities was found around the Jangga river including detergent and waste from agricultural and fisheries activity around the Jangga river.